Critical Incidents in the Reflective Practice of Science Teacher Education Science Teacher Training - Turpo-Gebera, Osbaldo; Diaz-Zavala, Rocio; Mango-Quispe, Pedro; Araujo-Castillo, Rey; Delgado-Sarmiento, Yvan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The analysis of critical incidents in the pre-professional practice of teacher training is essential to promote reflection. Building upon this notion, the urgent need for a reflective practice in the training of science teachers is addressed. In this context, future educators are instructed in the preparation of reports that highlight the critical incidents experienced in their pedagogical work. From these perspectives, reflective practice emerges as a fundamental resource to solidify their identity and pedagogical mastery by incorporating experiences for guidance purposes, emphasizing the significance of reflection.